Biomimetic Donor–Acceptor Motifs in Conjugated Polymers for Promoting Exciton Splitting and Charge Separation. Issue 28 (14th June 2018) - Ou, Honghui; Chen, Xinru; Lin, Lihua; Fang, Yuanxing; Wang, Xinchen
Abstract: Natural photosynthesis serves as a model for energy and chemical conversions, and motivates the search of artificial systems that mimic nature′s energy‐ and electron‐transfer chains. However, bioinspired systems often suffer from the partial or even large loss of the charge separation state, and show moderate activity owing to the fundamentally different features of the multiple compounds. Herein, a selenium and cyanamide‐functionalized heptazine‐based melon (DA‐HM) is designed as a unique bioinspired donor–acceptor (D‐A) light harvester. The combination of the photosystem and electron shuttle in a single species, with both n‐ and p ‐type conductivities, and extended spectral absorption, endows DA‐HM with a high efficiency in the transfer and separation of photoexcited charge carriers, resulting in photochemical activity. This work presents a unique conjugated polymeric system that shows great potential for solar‐to‐chemical conversion by artificial photosynthesis. Abstract : Melon motifs : Biomimetic donor–acceptor motifs were introduced in melon‐based carbon nitride semiconductors to promote exciton dissociation and charge separation. This work presents a simple version of a biomimetic polymeric system that shows great potential for solar‐to‐chemical energy conversion through artificial photosynthesis, and it provides the structural basis for designing photochemical conversion systems having bioinspired functions.